EFFECTS OF NITROGEN ON OIL YIELD AND ITS COMPONENT OF CALENDULA (CALENDULA OFFICINALIS L) IN DROUGHT STRESS CONDITIONS - Farahani, H. A.; Valadabadi, A.; Rahmani, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This experiment was conducted at Iran Research Institute of Forest and Rangelands in 2006. Field experiment was carried out by a split plot design with 4 replications. The factors which studied were irrigation according with 50, 100 and 150 mm water evaporation from evaporation pan and 0, 35, 70 and 105 kg ha-1 nitrogen. The results showed that drought stress significant effect on oil yield, seed yield, oil percent, seed thousand weight and seeds of head (α=1%). Means comparison showed that highest oil yield, seeds of head, seed thousand weight and seed yield with 505.3 kg ha-1, 25.67 mm, 31 seeds, 15.18 g and 3044 kg ha-1 were achieved under irrigation according 50 mm evaporation and highest oil percent with 24.15 percent was achieved under irrigation according 150 mm evaporation. Also nitrogen significant effect on oil yield, seed yield, oil percent, seed thousand weight and seeds of head (α=1%). Means comparison showed that highest oil yield, seed thousand weight, seed yield and seeds of head with 377.4 kg ha-1, 12.66 g, 1998 kg ha-1, 23.96 mm and 29.25 seeds were achieved under application of 105 kg ha-1 nitrogen and highest oil percent with 22.16 percent was achieved under application of 70 kg ha-1 nitrogen. Drought stress and application of 60 kg ha-1 nitrogen were increased oil percent but oil yield of calendula decreased in these conditions. Key words: Calendula, drought stress, nitrogen and oil yield.